Transmesenteric hernia in a peripartum patient: An unusual diagnosis - Ravi, Gopala Krishnan; Kumar, A K Ajith; Karanth, Sunil; Palankar, Nagaraj; Ramachandra, Shilpa (Indian Journal of Case Reports, 2020)
Congenital transmesenteric hernia is a very rare cause of intestinal obstruction in adulthood. We report a patient who came to the emergency with persistent abdominal pain post-emergency cesarean section and subsequently diagnosed to have acute pancreatitis based on computed tomography findings and elevated pancreatic enzymes. The pain was disproportionate to the diagnosis of pancreatitis and her condition rapidly got worsened requiring multiorgan support. Reimaging revealed obstructed transmesenteric hernia. The patient required immediate surgical intervention. A high index of the suspicion of internal hernia as one of the differential diagnoses of any atypical acute abdomen and early intervention could be lifesaving.